Parvovirus enteritis in sn immune pup following vaccination with multivalent live viral vaccines - Tham, K. M.; Dhaliwal, Gurmeet Kaur; Liow, S. L.; Abdul Rahman, Sheikh Omar (Persatuan Doktor Veterinar Malaysia, 1986)
Clinical signs ofcanine parvovirus (CPV) enteritis namely bloody diarrhoea and vomiting, developed in a three-month old pup on day 5 following vaccination with multivalent vaccines that contained modified live CPV, canine distemper virus (CDV}, adenovirus type 2 and parainfluenza virus. While postmortem examination showed a severe haemorrhagic enteritis and severe villous atrophy, laboratory findings showed that the rectal contents of the pup had a haemagglutination (HA) titre of 320 which was inhibited by a CPV reference serum. Prevaccination serum collected from the pup contained haemagglutination inhibition (HI) antibody at a titre of 320. These clinico-pathological and laboratory. findings suggest a case of CPV vaccination breakdown in an immune pup